Analysis Of Performance Supporting Factors For Micro, Small, And Medium Enterprises In KU-TAI Kartanegara Regency - Feriska Ajeng Anantri (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
Poverty is not only a crucial economic problem because it tends to increase and result in instability in various sectors of life, so handling it needs to be a shared responsibility. Regions that are rich in mineral resources also still have problems of poverty and unemployment, including in the Banua Enam region, South Kalimantan Province. This research analyzes the influence of mining sector growth, unemployment, and the capital expenditure ratio on poverty levels in the Banua Enam region, South Kalimantan Province. This type of research is explanatory and focuses on testing existing theories in the context of other research using panel data regression for 6 districts and 12 years. The results of this research suggest that the growth of the mining sector, unemployment, and the capital expenditure ratio, both partially and simultaneously, have a positive and significant effect on the poverty level. In other words, the higher the unemployment, the higher the poverty level. However, the higher growth of the mining sector and the capital expenditure ratio also increase poverty. Therefore, policies are needed that are pro-poor so that the growth of the mining sector and increased capital expenditure can overcome the problem of poverty.